Multi-response optimizations for high speed ductile mode machining of soda lime glass - Bagum, Nasima; Amin, A. K. M. Nurul; Konneh, Mohamed; Mohd Zaib, Noor Fathiah (Asian Research Publishing Network (ARPN), 2015)
Ductile regime end milling of soda lime glass needs consideration from commercial standpoints as well as in research and development. High speed machining is capable to obtain ductile mode at an increased material removal rate and at the same time tool wear rate can be optimized at higher value of cutting speed. This paper presents a simple and workable approach to process parameters optimization, to achieve ductile mode machining of soda lime glass applying high speed using the experiment design and parameter optimization capabilities of Response Surface Methodology (RSM). The particular ranges of cutting parameters were chosen based on initial tests conducted to ensure ductile mode machining during the experiments. The machining parameters such as cutting speed, depth of cut, and feed rate were varied from 30000 to 50000 rpm, 20 to 50 μm and from 45 to 75 mm/min (0.45 to 1.25 μm per tooth) respectively. Based on the experimental results empirical mathematical models relating the machining parameters to response parameters, namely, surface roughness, tool wear and tool life, were first developed. Multi-criteria optimization was conducted applying the desirability function of RSM based on the developed models, with the aim of determining the combination of machining parameters that would lead to optimal settings of responses. The quality criteria considered to establish optimal parameters were the minimization of surface roughness (Ra), tool wear (Tw) and maximization of tool life (Tl). Obtained results demonstrated that optimal combination of the response parameters, 0.78 μm Ra, 107 μm (Tw) and 0.56 min (Tl) were achieved with maximum desirability 77%, at the lowest depth of cut 20 μm at spindle speed of approximately 40000 rpm with feed rate of 69 mm/min.